4G Network Security Algorithms: Overview - M. Zaki, Rana; Bahjat Abdul wahab, Hala (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Long Term Evolution (LTE) of (Universal Mobile Telecommunication System) is one of the modern steps in series of mobile telecommunications systems. That appears to be a strong technology that meets the requirements of fourth-generation (4G) mobile networks and supports authentication and encryption mechanisms between User Equipment (UE) and Message Management Entity (MME). This paper provides an overview of the three most important algorithms that are considered the heart of LTE cryptographic algorithms (SNOW3G, AES, and ZUC) and a comparison between cipher key length and initial vector length to generate keystream depending on the structure used for each algorithm as each algorithm has a time of complexity and space of complexity that differs from the other security algorithm.